DYNAMICS OF LAND COVER CHANGE IN CIREBON URBAN AREA AND ITS SUITABILITY TO SPATIAL PLAN - Rizki, Muhammad
Cirebon National Activity Center (PKN) is a PKN that is encouraged to develop through strategic projects in the form of various infrastructure developments. The increasing rate of population growth is accompanied by a high demand for built-up land. Both of these have implications for the dynamic use of space in the Cirebon Urban Area as part of PKN Cirebon. On the other hand, spatial plan is a spatial utilization control instrument that serves to ensure environmental quality and sustainable development. This study aims to identify the dynamics of land cover change and its suitability for spatial plan in the Cirebon Urban Area. Land cover data for 2014, 2018, and 2022 were obtained from Landsat 8 image processing. Factors driving land cover change were identified using binary logistic regression. Land cover data and driving factors were then used as input in land cover modeling using MOLUSCE in QGIS. The results of the analysis show that land cover change in the Cirebon Urban Area is dominated by vegetation cover and agricultural land converted to built-up land. The land cover change was driven by distance to arterial roads, distance to the city center, and surface temperature. LR-CA-Markov modeling with an accuracy of 66.66% was used to predict land cover in 2038. Comparison of land cover in 2038 with the spatial pattern plan in Cirebon Urban Area resulted in a percentage of conformity of 57.72%, indicating that the spatial utilization in Cirebon Urban Area is not fully in accordance with the spatial plan. The results of land cover modeling with Cellular Automata can be used as input in spatial planning, especially to anticipate potential spatial deviations in the Cirebon Urban Area.